2000
DOI: 10.1116/1.1316102
|View full text |Cite
|
Sign up to set email alerts
|

Reaction layer dynamics in ion-assisted Si/XeF2 etching: Temperature dependence

Abstract: We study the dynamics of the reaction layer during Ar ϩ ion-assisted Si etching by XeF 2 in the temperature range Tϭ150-800 K. Depending on temperature, the etch rate can be enhanced a factor of 8 by ion bombardment. The dynamics are studied with ion-pulse measurements on a time scale of 1-100 s in a molecular beam setup. A reaction layer with a submonolayer fluorine coverage and dangling bonds is found to be formed on the Si͑100͒ surface during ion bombardment. The dangling bond concentration increases with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…The values of reaction rate constants and frequencies, found by extrapolation from experimental data, are presented in Table. It is observed that ion bombardment increases adsorption of XeF 2 molecules and C x H y molecules. The obtained theoretical results are in agreement with experimental measurements [24]. The removal frequencies of XeF 2 , SiF 4 molecules, and Xe atoms increase in the presence of ion bombardment.…”
Section: Resultssupporting
confidence: 88%
“…The values of reaction rate constants and frequencies, found by extrapolation from experimental data, are presented in Table. It is observed that ion bombardment increases adsorption of XeF 2 molecules and C x H y molecules. The obtained theoretical results are in agreement with experimental measurements [24]. The removal frequencies of XeF 2 , SiF 4 molecules, and Xe atoms increase in the presence of ion bombardment.…”
Section: Resultssupporting
confidence: 88%